Effectiveness of Halal Certification Labels on Halal Cuisine at Beach Tourist Sites on Tourists' Customer Satisfaction and Behavioral Intention - Novrianda, Herry; Muttaqin, Faisal (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2024)
Purpose: This study aims to explore the impact of halal certification on tourist satisfaction and behavioral intention. The primary focus is to understand the extent to which halal certification influences the experiences of tourists within the context of halal culinary offerings.Design/methodology: The research employs an experimental methodology, with an experimental design structured as (visual label, textual label) x 2 (halal content warning label, non-label) between subjects. The study involves 120 tourists visiting various attractions across Bengkulu Province. Participants were randomly assigned to different experimental cells, each exposed to distinct stimuli, to assess the effects of halal certification.Findings: The results of the study support all proposed hypotheses. The halal certification label on halal culinary products has a significant positive effect on customer satisfaction. Additionally, the presence of halal certification significantly influences tourists' behavioral intentions.Practical implications: The findings of this research provide valuable insights for policymakers, particularly government authorities, in formulating and enhancing policies related to halal certification and tourism development in Indonesia.Originality/Value: This research contributes to the literature by addressing a theoretical gap concerning the effectiveness of halal certification in the context of halal tourism. The study offers a substantial academic contribution, with implications for policy formulation in the tourism sector.